Life Cycle Analysis of Decentralized Preprocessing Systems for Fast Pyrolysis Biorefineries with Blended Feedstocks in the Southeastern United States. Issue 11 (3rd September 2019) - Lan, Kai; Ou, Longwen; Park, Sunkyu; Kelley, Stephen S.; Yao, Yuan
Abstract : Blending biomass feedstock is a promising approach to mitigate supply chain risks that are common challenges for large‐scale biomass utilization. Understanding the potential environmental benefits of biofuels produced from blended biomass and identifying driving parameters are critical for the supply chain design. Herein, a cradle‐to‐gate life cycle analysis model for fast pyrolysis biorefineries converting blended feedstocks (pine residues and switchgrass) with traditional centralized and alternative decentralized preprocessing sites, so‐called depots, is explained. Different scenarios are developed to investigate the impacts of parameters such as feedstock blending ratios, biorefinery and depot capacities, preprocessing technologies, and allocation methods. The life‐cycle energy consumption and global warming potential (GWP) of biofuel production with depots vary between 0.7–1.1 MJ MJ −1 and 43.2–76.6 g CO2  eq. MJ −1, respectively. The results are driven by biorefinery processes and depot preprocesses. A decentralized design reduces the energy consumption of the biorefinery but increases the overall life‐cycle energy and GWP. Such increases can be significantly mitigated by increasing switchgrass content as the energy consumption at the depot is driven largely by the higher moisture content of pine feedstocks. Allocation methods also have a large impact on the results but do not change the major trends and overall conclusions. Abstract : This study conducts a cradle‐to‐gate life cycle analysis (LCA) on fast pyrolysis biofuel production with decentralized preprocessing sites and blended biomass feedstocks, pine residues and switchgrass. The results are compared with a traditional centralized biorefinery design and the key driving factors are identified.